2021
DOI: 10.1177/1350650120987033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the inlet oil temperature on vibration characteristics of the high-speed turbocharger rotor system

Abstract: The inlet oil temperature of the rotor system with high-speed and light-load turbocharger will change during operation, which will change the vibration characteristics of the rotor system and even cause vibration accidents. Taking a certain type of high-speed and light-load turbocharger rotor system as the research object, the changes in oil film viscosity, friction power consumption, oil film temperature rise, and ring speed ratio with the inlet oil temperature of floating ring bearings are analyzed. A dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Andrés et al 25,26 made further predictions of the linear as well as nonlinear behavior in the turbocharger rotor system and compared the predicted results with experimental data. Zhong et al, 27 Wang et al, 28 and Bin et al 29,30 studied the effect of unbalanced and inlet oil temperature on the vibration of the turbocharger rotor. It has been found that the rotor vibration condition was best when the inlet oil temperature of the floating ring bearing was 90 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Andrés et al 25,26 made further predictions of the linear as well as nonlinear behavior in the turbocharger rotor system and compared the predicted results with experimental data. Zhong et al, 27 Wang et al, 28 and Bin et al 29,30 studied the effect of unbalanced and inlet oil temperature on the vibration of the turbocharger rotor. It has been found that the rotor vibration condition was best when the inlet oil temperature of the floating ring bearing was 90 °C.…”
Section: Introductionmentioning
confidence: 99%